Travelling Wave Solutions of the K(n, n) Equation - İnç, Mustafa; Ates, Esma (Elsevier, 2015)
This paper addresses the Jacobi elliptic function method and applies it to the K(n, n) equation. New traveling wave solutions are obtained which can be expressed in terms of Jacobi elliptic functions. The compacton, solitary pattern, periodic, and rational solutions are also retrieved.
Keywords: F-Expansion Method; Soliton-Solutions; (G'/G)-Expansion Method; Nonlinear-Waves; Boussinesq; Compact; Tanh; Burger